2020
DOI: 10.3349/ymj.2020.61.9.750
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal CircPRRX1 Enhances Doxorubicin Resistance in Gastric Cancer by Regulating MiR-3064-5p/PTPN14 Signaling

Abstract: Purpose Gastric cancer (GC) is a malignant tumor with a high mortality rate. Drug resistance is a major obstacle to GC therapy. This study aimed to investigate the role and mechanism of exosomal circPRRX1 in doxorubicin resistance in GC. Materials and Methods HGC-27 and AGS cells were exposed to different doses of doxorubicin to construct doxorubicin-resistant cell lines. Levels of circPRRX1, miR-3064-5p, and nonreceptor tyrosine phosphatase 14 (PTPN14) were detected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…In addition, exosome-derived miR-155-5p is efficiently taken up by MGC-803 cells, which were sensitive to paclitaxel, subsequently inducing paclitaxel-resistance in an autocrine manner [84]. A high level of circPRRX1 expression was observed in HGC-27 and AGS doxorubicin-resistant GC cell lines, and further research showed that circPRRX1 spread doxorubicin resistance via exosomes [85]. In addition, mechanistic assays found that circPRRX enhanced doxorubicin resistance by sponging miR-3064-5p or regulating expression levels of PTPN14.…”
Section: Drug Resistancementioning
confidence: 96%
“…In addition, exosome-derived miR-155-5p is efficiently taken up by MGC-803 cells, which were sensitive to paclitaxel, subsequently inducing paclitaxel-resistance in an autocrine manner [84]. A high level of circPRRX1 expression was observed in HGC-27 and AGS doxorubicin-resistant GC cell lines, and further research showed that circPRRX1 spread doxorubicin resistance via exosomes [85]. In addition, mechanistic assays found that circPRRX enhanced doxorubicin resistance by sponging miR-3064-5p or regulating expression levels of PTPN14.…”
Section: Drug Resistancementioning
confidence: 96%
“…At present, there are relatively few research reports on miR-3064-5p, and the studies mainly focus on tumor-related fields. In our study, we noticed that miR-3064-5p was significantly up-regulated in EAT-derived exosomes from CAHD patients, and its inhibitor could obviously improve the inhibitory effect of CAHD-derived exosomes on the adipogenic differentiation of EASCs ( 13 , 14 ). Further analysis showed that Nnat is the target gene of miR-3064-5p in EASCs.…”
Section: Discussionmentioning
confidence: 71%
“…Furthermore, it was reported that exosome miR-155-5p directly inhibits GATA3 (GATA binding protein 3) and TP53INP1 (tumor protein p53-induced nuclear protein 1) to induce paclitaxel resistant GC cells to sensitive ones (67). And Wang SM (68) found that exosomal circPRRX1 (circular paired-related homeobox 1) strengthened doxorubicin resistance of GC cells by modulating miR-3064-5p/PTPN14 (non-receptor tyrosine phosphatase 14) signaling pathway.…”
Section: Exosomesmentioning
confidence: 99%